Mothers’ experiences and perceptions about care provided during home deliveries in Alwa sub county, Kaberamaido district, Uganda– a qualitative study - Dektar, Benbella; Beckford, Anita Normans; Kemba, Jonny; Crayson, Belinda (Frontiers in Public Health, 2023)
Introduction In Uganda 27% of deliveries take place outside a health facility. The existing gaps in quality of maternal and newborn health care must be addressed for Uganda to attain its health targets and consequently its economic targets. Some of the gaps include but are not limited to; ill-equipped healthcare facilities in rural settings, inadequate client/customer care skills by healthcare providers, and health worker absenteeism especially in the night hours. In Kaberamaido District, only 38.3% of the deliveries in Alwa sub county took place at a health facility. Despite the district local government and stakeholder efforts to promote health facility-based deliveries, sadly, a very low proportion of women use the health facilities for delivery. We sought to explore mothers’ experiences and perceptions about care provided during home deliveries in Alwa sub county, Kaberamaido district. Methods The study adopted a cross-sectional descriptive qualitative design. We purposively included 115 mothers who delivered outside the health facility and consented to participate and those who lost their babies within the last 24 months preceding the study. Other participants included in the study were village health team (VHT), traditional birth attendants (TBA) and older women. The main instruments used to collect data were focus group discussion (FGD) and in-depth interview (IDI) guides. All voice recordings from FGDs and interviews were transcribed and translated from the local language (Kumam) into English. Thematic content analysis was used to synthesize data by applying codes to segments of the transcripts upon which major domains were derived. Key findings were synthesized and quotes were carefully selected based on their relevance and representativeness to the analysis and study objective. Results Our findings indicated general satisfaction with the care provided during and after home delivery by TBAs as expressed by mothers. Motivation to seek services from TBAs was attributable to their vast experience spanning decades with history of safe delivery. Few mothers expressed discontent with TBA services citing abuse and rudeness. Discussion Our study underscored the common view that TBAs effectively managed home deliveries, providing satisfactory care to mothers. However, concerns emerged on TBAs’ capacity to manage complications, emphasizing a need for their reintegration into formal healthcare systems, alongside further training, and standardization in maternal care practices.